Under pressure: accounting for multiple human pressures outside and inside marine protected areas in the Skagerrak - Helene Frigstad; Jesper H. Andersen; Trine Bekkby; Linus Hammar; Ashley D. Hemraj; Dag O. Hessen; Tobias K. Mildenberger; Even Moland; Ciarán J. Murray; Helle M. Sommer; Andy Stock; Johanna M. Aarflot; et al. (Frontiers in Marine Science, 2026)
The combined effects of multiple pressures pose critical threats to marine ecosystems. As an initial spatial assessment of cumulative pressures in the Skagerrak, we mapped where multiple pressures coincided with sensitive habitats and species, combining recent spatial data sets on 20 pressures and 39 habitats and species. The spatial data were linked with sensitivity weights obtained with a novel partly data-driven method. We found major spatial variation in the risk of cumulative impacts, identifying areas with high human impact, termed hot spots (such as shallow areas in southern and eastern Skagerrak), and areas with low human impact, termed cold spots (such as the deeper parts of the Norwegian Trench). The dominating human pressures were 1) fishing activities, 2) climate change, 3) underwater noise, 4) input of contaminants, 5) light pollution and 6) input of nutrients. Analyses of human pressures within and outside 20 Marine Protected Areas (MPAs) indicated significantly reduced levels in nine MPAs; however, these reductions were limited (less than 15%). One MPA (Skagens Gren og Skagerrak, DK) had significantly higher total human pressure inside the protected area, while ten MPAs did not yield significant results. We therefore recommend that the conservation measures in MPAs in the region be critically addressed and human pressures mitigated, to reduce the potential negative impact of human activities.

Incorporating ecosystem component interactions and indirect effects in cumulative impact assessment models - Iréne Wåhlström; Diana Perry; Sanne Bergman; Martin Dahl; Maria E. Granberg; Martin Gullström; Linus Hammar Perry; Kerstin Magnusson; Peter Thor (Journal of Environmental Management, 2025)

Projected climate change impact on a coastal sea—As significant as all current pressures combined - Iréne Wåhlström; Linus Hammar; Duncan Hume; Jonas Pålsson; Elin Almroth‐Rosell; Christian Dieterich; Lars Arneborg; Matthias Gröger; Martin Mattsson; Lovisa Zillén Snowball; Gustav Kågesten; Oscar Törnqvist; et al. (Global Change Biology, 2022)
Climate change influences the ocean's physical and biogeochemical conditions, causing additional pressures on marine environments and ecosystems, now and in the future. Such changes occur in environments that already today suffer under pressures from, for example, eutrophication, pollution, shipping, and more. We demonstrate how to implement climate change into regional marine spatial planning by introducing data of future temperature, salinity, and sea ice cover from regional ocean climate model projections to an existing cumulative impact model. This makes it possible to assess climate change impact in relation to pre‐existing cumulative impact from current human activities. Results indicate that end‐of‐century projected climate change alone is a threat of the same magnitude as the combination of all current pressures to the marine environment. These findings give marine planners and policymakers forewarning on how future climate change may impact marine ecosystems, across space, emission scenarios, and in relation to other pressures.

Expanding the concept of sustainable seafood using Life Cycle Assessment - Friederike Ziegler; Sara Hornborg; Bridget S Green; Ole Ritzau Eigaard; Anna K Farmery; Linus Hammar; Klaas Hartmann; Sverker Molander; Robert W R Parker; Erik Skontorp Hognes; Ian Vázquez‐Rowe; Anthony D M Smith (Fish and Fisheries, 2016)
Fisheries management and sustainability assessment of fisheries more generally have recently expanded their scope from single‐species stock assessment to ecosystem‐based approaches, aiming to incorporate economic, social and local environmental impacts, while still excluding global‐scale environmental impacts. In parallel, Life Cycle Assessment ( LCA ) has emerged as a widely used and recommended framework to assess environmental impacts of products, including global‐scale impacts. For over a decade, LCA has been applied to seafood supply chains, leading to new insights into the environmental impact of seafood products. We present insights from seafood LCA research with particular focus on evaluating fisheries management, which strongly influences the environmental impact of seafood products. Further, we suggest tangible ways in which LCA could be taken up in management. By identifying trade‐offs, LCA can be a useful decision support tool and avoids problem shifting from one concern (or activity) to another. The integrated, product‐based and quantitative perspective brought by LCA could complement existing tools. One example is to follow up fuel use of fishing, as the production and combustion of fuel used dominates overall results for various types of environmental impacts of seafood products, and is also often linked to biological impacts of fishing. Reducing the fuel use of fisheries is therefore effective to reduce overall impacts. Allocating fishing rights based on environmental performance could likewise facilitate the transition to low‐impact fisheries. Taking these steps in an open dialogue between fishers, managers, industry, NGO s and consumers would enable more targeted progress towards sustainable fisheries.